The heavenly sanctuary/temple motif in the Hebrew bible: function and relationship to earthly counterparts - Souza, Elias Brasil de (Kerygma, 2007)
The present dissertation seeks to ascertain the function of the heavenly sanctuary/temple and its relationship to earthly counterparts, as reflected in forty-three passages of Hebrew Bible. Thus, following an introductory chapter, the second chapter of this dissertation is devoted to a survey of the heavenly sanctuary temple motif in the ANE literature as represented by Sumerian, Akkadian, Hittite, Ugaritic, and Egyptian texts. The investigation of these texts reveals that the heavenly sanctuary/temple motif was part of the worldview of the ANE, where the heavenly sanctuary was not only assumed as existing in heaven, but also as functioning in close relationship to the earthly counterparts. Chapters 3, 4, and 5 are devoted to the exegesis of heavenly sanctuary/temple passages in the Hebrew Scriptures, according to thecanonical divisions of the Hebrew Bible (namely Torah, Prophets, and Writings). This investigation reveals the pervasive presence of the that the heavenly sanctuary/temple motif in the Hebrew Bible and provides a broad delineation of its function and relationship to earthly counterparts. It has been found that the heavenly sanctuary temple functions as a place of divine activities where YHWH supervises the cosmos, performs acts of judgment (sometimes conceived as a two-stage activity in which the execution of the sentence was preceded by an investigative phase), hears the prayers of the needy, and bestows atonement and forgiveness upon the sinners. The perceptions also emerged of the heavenly sanctuary/temple as a place of worship, a meeting place for the heavenly council, and an object of attack by anti-YHWH forces, thus playing a pivotal role in the cosmic battle between good and evil. In terms of its relationship to the earthly counterpart, it has become apparent that the heavenly sanctuary/temple was understood to operate in structural and functional correspondence to the earthly counterparts. Some texts display a dynamic interaction inasmuch as the heavenly and earthly sanctuaries/temples are conceived of as working in close connection so that the activities being performed in one would reverberate in the other. Chapter 6 presents theological synthesis of the heavenly sanctuary/temple motif based on the previous chapters. Thus, some consideration was given to the similarities and differences between the heavenly sanctuary/temple motif as found in the Hebrew Bible and in its ANE background. Next, attention is devoted to some theological implications of the heavenly sanctuary/temple motif for the notions of judgment, the great controversy between good and evil. To conclude, the notion emerges that the Hebrew Bible conceives of the heavenly sanctuary/temple in functional and structural correspondence with its earthly counterpart with both sanctuaries/temples operating dynamic interaction.